In vitro antioxidant and anti-atherosclerotic activities of phenolic saponin rich fraction of Cosmos caudatus kunth - Moshawih, Said Faroq Saiyid (2016)
Cosmos caudatus or Ulam raja as it is known in Malaysia, is a tropical plant that has been known in South East Asia for many traditional uses, some were proved by pharmacological studies, while others yet to be validated. In this study, we are inspecting the atheroprotective effects for ulam raja extract/fractions through in vitro. The shoot samples were collected fresh from the plant stem, oven dried and grinded. A 100 gm sample was macerated in 50% (v/v) ethanol, twice for 48hours each time with intermittent shaking, after extract pooling, solvent was removed under reduced pressure and lyophilized to produce the crude extract. Subsequently, the crude extract was fractionated to produce the butanol and the aqueous fractions. In order to determine the phenolic, saponin and steroidal saponin contents, we employed folinciocalteu, vanillin-sulfuric acid and anisaldehyde-sulfuric acid methods respectively. Butanol fraction was the phenolic-saponin rich fraction (PSRF) due to the fact that it possesses the richest total phenolic, saponin and steroidal saponin contents (88.45 mg GAE/g DW, 64.23 and 23.3 mg DE/g DW) respectively (P<0.05), compared to the other C. caudatus derived fractions. Similarly, butanol fraction showed the highest antioxidant activity in four assays namely, DPPH, ABTS, iron chelating and BCB activity assays. Antioxidant activities for butanol fraction were (72.65 mg TEAC/ g DW), (94.47 mg TEAC/ g DW), (16.03 mg EDTA/ g DW) and (19.43 mg TEAC/ g DW) respectively. Cytotoxic effects of crude, butanol and aqueous fractions were determined by MTT assay in rat aortic smooth muscle cell line (A-10) for 24 hours, and IC50 were as follows 460.78, 313.96 and 949.2 μg/mL respectively. IC50 for the three fractions was going in the same trend of the previous assays, as butanol was the most potent, followed by crude, and lastly the aqueous fraction. Three concentrations (IC10, IC25 and IC50) of the three fractions were used to treat A-10 cell line to assess their activities in inhibiting migration and invasion of cells using Boyden chamber assay. Butanol fraction Intermediate concentration (IC25) demonstrated the strongest activity to inhibit smooth muscle cells from migration and invasion in in vitro assays, as they were reduced by 53.93% and 59.94% respectively compared to untreated control cells. However, the invasion inhibition index referred to that butanol and crude mild concentrations (IC10) showed the highest index value ~68%, which means the best cell invasion to cell migration inhibition in vitro. Taken together, results strongly support that PSRF from C. caudatus can be used to reduce atherosclerotic plaque formation by reducing its key mechanism represented by SMCs migration and invasion, and its subsequent events such as myocardial infarction and strokes. This can be attributed to the high contents of phenolics, saponins and vitamins, and their ability to reduce the oxidative stress and free radicals, in addition to the other mechanism of action of other flavonoids.